Model Kepemimpinan Transformasional terhadap Disiplin Kerja Pegawai Melalui Komitmen Organisasi di Poltekkes Kemenkes Malang - Afnani Thoyibah; Achmad Supriyanto; Aan Fardani Ubaidillah (CV. Global Cendekia Inti, 2026)
This study examines the mediating role of organizational commitment in the relationship between transformational leadership and employee work discipline in health vocational education institutions. A quantitative cross-sectional survey was conducted with 220 employees from Poltekkes Kemenkes Malang, Indonesia. Data were collected using validated instruments and analyzed using PLS-SEM. Results revealed that transformational leadership significantly influenced work discipline both directly (β = 0.186, p < 0.01) and indirectly through organizational commitment (β = 0.409, p < 0.001). The model demonstrated partial mediation with VAF of 68.74%, indicating that organizational commitment serves as a crucial mechanism. Organizations should prioritize developing transformational leadership competencies and fostering organizational commitment to enhance employee discipline sustainably